2013
DOI: 10.1016/j.jinf.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and viral interactions within the nasopharynx contribute to the risk of acute otitis media

Abstract: Summary Objectives To understand relationships between microbes in pathogenesis of acute otitis media during respiratory tract infections, we compared nasopharyngeal bacteria and respiratory viruses in symptomatic children with and without AOM. Methods We enrolled children (6–35 months) with acute symptoms suggestive of AOM and analyzed their nasopharyngeal samples for bacteria by culture and for 15 respiratory viruses by PCR. Non-AOM group had no abnormal otoscopic signs or only middle ear effusion, while A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 35 publications
(37 reference statements)
5
58
0
1
Order By: Relevance
“…Coinfection with S. pneumoniae and IAV is linked both experimentally and epidemiologically with the development of OM (6,7,45). The activity of the viral neuraminidase altering the respiratory and eustachian tube epithelium has long been proposed to be a mechanism by which preceding IAV infection potentiates the initiation of this disease by pneumococci (15,46).…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with S. pneumoniae and IAV is linked both experimentally and epidemiologically with the development of OM (6,7,45). The activity of the viral neuraminidase altering the respiratory and eustachian tube epithelium has long been proposed to be a mechanism by which preceding IAV infection potentiates the initiation of this disease by pneumococci (15,46).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic evidence strongly indicates a role for upper respiratory tract viruses, particularly influenza A virus (IAV), in the dissemination of S. pneumoniae from its nasopharyngeal niche to the middle ear (7)(8)(9)(10)(11). Indeed, experimental IAV infection of human volunteers was shown to increase both nasal pneumococcal burden and incidence of OM (12,13).…”
mentioning
confidence: 99%
“…The development of mouse models, though often requiring either the use of artificial or invasive procedures (17,18) or infant mice (19)(20)(21), has further significantly contributed to and widened the field. Largely stemming from these models, the viral factors which predispose to OM are well-studied and include eustachian tube dysfunction, ciliary dysmotility, mucosal inflammation, and neutrophil impairment (8,11,(22)(23)(24). How this viral predisposition affects specific pneumococcal subpopulations during middle ear infection, however, is less well understood.…”
mentioning
confidence: 99%
“…While previous studies have also shown that Gram-negative organisms are more commonly found colonizing the respiratory tract of formula-fed infants than breastfed infants, 39-41 these studies were not undertaken in HIV-exposed infants. Furthermore, while prior studies have shown that colonization by Gram-negative organisms can lead to an increased risk of otitis media and other upper respiratory tract infections in healthy infants, [42][43][44] our results suggest that it could also increase the risk of lower respiratory tract infection outside intensive care units and in non-cystic fibrosis patients. Despite the association between Gram-negative colonization and increased pneumonia, this study did not find Gram-negatives to be a common cause of pneumonia by blood culture (though all Gram-negative pneumonias occurred in formula-fed infants).…”
Section: Discussionmentioning
confidence: 44%